False Friends in Translation: A Lexical Source of Interference in English–Azerbaijani Contexts - Kamala Avadir Jafarova (Journal of linguistics, culture and communication, 2025)
This paper examines the phenomenon of “false friends” as a critical source of lexical interference in the translation process. False friends—lexical items that appear phonologically or orthographically similar across languages but diverge semantically—frequently mislead translators into selecting inaccurate equivalents. These deceptive similarities often result in distortions of the source text’s intended meaning, particularly among individuals with limited bilingual competence, thereby compromising the overall translational adequacy. The present study aims to assess the extent to which false friends contribute to lexical interference and to underscore the importance of linguistic awareness and systematic training in translator education. In an era of intensifying global communication and escalating demand for high-quality translation services, this issue holds substantial relevance. Lexical inaccuracies arising from false friend interference can impede comprehension, facilitate cultural misinterpretation, and pose reputational risks across academic, professional, and diplomatic spheres. To address this challenge, the paper outlines methodological strategies for identifying and categorizing false friends and advocates for their explicit integration into translation pedagogy. Enhancing translators’ sensitivity to these lexical pitfalls enables more accurate, context-aware lexical choices. Ultimately, minimizing the impact of false friends not only improves the semantic precision of translations but also promotes more effective intercultural exchange in multilingual contexts.